2022
DOI: 10.1183/23120541.00451-2022
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model combining patient-reported outcome measures, spirometry and exhaled nitric oxide fraction for asthma diagnosis

Abstract: INTRODUCTIONAlthough asthma is a common disease, its diagnosis remains a challenge in clinical practice with both over/under-diagnosis. Here, we performed a prospective observational study investigating the value of symptom intensity scales alone or combined with spirometry and FeNO to aid in asthma diagnosis.METHODSWe recruited, over a 38-month period, 303 untreated patients complaining with symptoms suggestive of asthma (cough, chest tightness, dyspnea, airway secretion and wheezing). The whole cohort was sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Other studies have also evaluated the role of FeNO in predicting asthma diagnosis in combination with other measurements. A recent study by Louis and colleagues demonstrated that a combination of wheezing scale, spirometry and FeNO improves the diagnostic accuracy with area under curve of 0.76 (95% confidence interval 0.66–0.84) [ 21 ]. In another study of 58 adults with persistent allergic rhinitis followed over 1 year showed that basal FeNO levels over 28 parts per billion (ppb) predicted development of asthma [ 22 ].…”
Section: Feno As a Diagnostic Biomarker For Asthmamentioning
confidence: 99%
“…Other studies have also evaluated the role of FeNO in predicting asthma diagnosis in combination with other measurements. A recent study by Louis and colleagues demonstrated that a combination of wheezing scale, spirometry and FeNO improves the diagnostic accuracy with area under curve of 0.76 (95% confidence interval 0.66–0.84) [ 21 ]. In another study of 58 adults with persistent allergic rhinitis followed over 1 year showed that basal FeNO levels over 28 parts per billion (ppb) predicted development of asthma [ 22 ].…”
Section: Feno As a Diagnostic Biomarker For Asthmamentioning
confidence: 99%